Utilization of, satisfaction toward, and challenges for Internet-based healthcare services provided by primary health institutions: Evidence from China - Wang, Shuo; Wang, Xin; Zhou, Yuyin; Xu, Junfang (Frontiers in Public Health, 2023)
Background The rapid development of “Internet plus healthcare” in China has provided new ways for the innovative development of primary healthcare. In addition, a series of favorable policies have been issued to promote Internet-based healthcare services in primary health institutions. Objective The aim of this study was to describe the utilization of, satisfaction toward, and challenges faced by Internet-based healthcare services provided by primary health institutions in China. Methods A self-designed structured questionnaire was employed to collect related data in January 2022 through Credamo. The questionnaire mainly included sociodemographic characteristics, health-related information, utilization of, satisfaction toward, and challenges faced by Internet-based healthcare services provided by primary health institutions. Descriptive analysis was used to describe the sociodemographic characteristics, utilization, satisfaction, and challenges by subgroups. The Wilcoxon rank-sum test was carried out to examine the differences in satisfaction with Internet-based healthcare services between participants who ever received these services and those who did not. A multiple logistic regression model was also used to examine the factors influencing the utilization of Internet-based healthcare services provided by primary health institutions. Results A total of 10,600 residents were included in the final analysis, of whom 5,754 (54.3%) were women. Overall, 51.3% (5,434) of the total participants ever used Internet-based healthcare services provided by primary health institutions. Among those who used Internet-based healthcare services, the most widely used services were procedure-related consultation services (63.7%). The satisfaction among those who ever used it was significantly higher than that among those who did not (84.7 vs. 45.4%; p-value < 0.001). One of the biggest challenges (69.3%) expressed by the residents was that it was difficult for the elderly to use Internet-based services, followed by community doctors with low capacity of providing primary care online (49.0%) and residents were worried about the information security and privacy protection (48.5%). Younger people, people with lower education levels, and people with chronic diseases were significantly more likely to use Internet-based healthcare services provided by primary health institutions (P < 0.05). Conclusion Among 10,600 residents surveyed in China in 2022, more than half of the people used Internet-based healthcare services provided by primary health institutions, and most of them were satisfied, although subgroups significant differences existed. The most common use was procedure-related (e.g., online registration and result query), and several challenges of using Internet-based healthcare services exist (e.g., information safety and usage among elderly people). Therefore, it is important to further improve Internet-based primary healthcare services based on the population perception of achieving healthy China in 2030.